PEMANFAATAN TEKNOLOGI DALAM PROSES PEMBELAJARAN MENUJU PEMBELAJARAN ABAD 21 - Darwin Effendi; Achmad Wahidy (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The application and adaptation of technology in learning spaces is a necessity in the face of changes in the era of globalization, the development of information and communication technology has had an influence on the world of education, especially in the learning process. Technological developments have led to innovative and creative learning models in the learning process. The network learning system (SPADA) has helped educators in facing the challenges of technological development. One learning model that can be applied in technological development is blended learning which is a combination of the advantages of face-to-face and virtual learning.